Timing the Timeless - Darielle Mason (21: Inquiries into Art, History, and the Visual)
This article reconstructs the physical and intellectual content of Stella Kramrisch’s 1968 exhibition Unknown India. Ritual Art in Tribe and Village, organized for the Philadelphia Museum of Art. By probing Kramrisch’s curatorial practice from conception to realization, it opens questions about her impact on canons and categories we continue to utilize today. In Unknown India, Kramrisch synthesized a vision rooted in the global Arts and Crafts movement and in India’s movement for cultural independence. But here she explicitly struggled with taxonomy, moving South Asia to the forefront of global dialogues on terms including folk, tribal, tradition, authenticity, craft, design, and even art. As contemporary scholars debate the dynamism of authenticity, the intersectionality of the spiritual and practical, and the fluidity of hierarchies, Unknown India remains a touchstone.